Akses Terhadap Putusan Lembaga Peradilan di Era Keterbukaan Informasi - Muhammad Insa Ansari (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: Rigth to information in one of the human right regulated in he 1945 Constitution. The implementation of such right for the citizen is further regulated in the Act Number 14, 2008 regarding the Openness of Public Information. This paper explores the information openness of the judicial intitution as a public institution. Basically, such openness is not the new thing in Indonesian justice procedure system. Article 195 f the Indonesian Penal Law states that all decision are valid and enforcable if it is stated in te open trial for the public. Aticle 13 (1) of the Act Number 48, 2009 regarding the Justice Authority also provides that each trial process is open for public unless he Act states conversely. Article 20 of he Act Number 4, 2004 regarding the Justice Power also states the same thing as the Act Number 48, 2009. however, the decision that is more accessible to public is the decision of the Supreme Court. Contrastly, the decision of the first instance court and the court of appeal have not been able to be accessed yet. Therefore, in the era of public information openness, such information should be easily and quickly accessed by the public through electronic and printed media court official websites, started from the court of the first intance. Miliatry Court, Administrative Court, Appeal Court to the Supeme Court. The Access to Judicial Decision in the Era Of Information Openness